Re-Eksistensi Peran Desa dalam Rantai Pasok Produksi Pengolahan Hutan Desa Melalui Bank Pohon: (Strategi Penegakan Hak Asasi Manusia Sektor Kehutanan) - Moh. Rif’an; Ivan Drago; Safira Niken Daniswara; Devi Arista Putri (Jurnal Hukum Lex Generalis, 2020)
The opening of the Indonesian Constitution is a noble agreement of the Indonesian nation to live together (Modus Vivendi) in a plural one-nation bond. Vivendi's modus, has given birth to the ideal of the state, which is the identity and guidance of the nation in stepping. Thus, the constitution has mandated the State to take responsibility for the welfare of the people. Indonesia has the second-largest tropical forest in the world with high economic value that can be managed by the state and society. This allows for the establishment of different types of crops and the utilization of economic aspects of forest products. In managing forest products it is unfortunate that it is still not optimal both with intensive and with the many requests for deforestation or conversion of forest land. Both planned deforestation and unplanned deforestation. On the other hand, Indonesia recognizes the existence of the Village Government and empowerment regarding the empowerment of rural communities which is a process to make the community improve the quality of life of the weak community for the better. Thus, it is necessary to re-initiate the role of the village government in the processing of village forests as one of the rights of the village community. The type of research used is normative juridical. Therefore, the author initiated a grand design of Village Forest Management to complement the processing and utilization of forest products integrated with the role of the Village Government as a system that aims to optimize the production supply chain as one of the important indicators of development and resilience of the country's economy in each region that uses variable forest products as their main income.